ANALISIS PENERIMAAN RETIBUSI PARKIR KOTA MANADO TAHUN 2008-2012 - Go, Edward Ricardo; Sondakh, Jullie; Wokas, Heince (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Parking retribution is one main source for Regional Original Revenue (PAD). The employment of regional autonomy in Indonesia makes parking retribution as one source of regional revenues. This research was done in Transportation Institution Office (DISHUB) Manado City and Parking Technical Executing Units (UPT) that responsible in handling parking retribution management. This research aims to analyze the development of parking retribution revenues, to forecast the realization of parking retribution effectiveness from 2016 until 2020, and to give insight for improving the parking retribution effectiveness in the future. The used analysis method is descriptive analysis method. Based on this research results, it is shown that UPT DISHUB Kota Manado have met the realization target of parking retribution revenues by Regional Government Manado, excellently and effectively. After the effectiveness analysis has been done, it can be concluded that the realization of parking retribution revenues is still increasing, starting from 61.20% at 2008, until reaching 111.46 at 2012. Based on the forecasting of parking retribution revenues amount from 2016 until 20120, it is simplified that the realization of parking retribution is always increasing, between 2012-2016, it has increased up to 385.83% until reach 361.04% at 2020. Based on those forecasting, for improving the effectiveness of this revenues, it is suggested to parking UPT for conducting enhancement, start from fee policy evaluation, HR efficiency and effectiveness to routine monitoring in TKP, and Natural Resources improvement or using computerized system to minimize indiscipline.